Analysis of loading of a cross-country skiing sprint competition simulation - Stöggl, T.; Lindinger, S.; Müller, E. (University of Salzburg, 2005)
The introduction of Sprint, Team Sprint and the improvement of equipment and technique allowing athletes to ski at higher speeds, led to new and altered demands in the training and testing of cross-country (XC) skiers. Due to still a lack of experience and the just developing specialisation of athletes on the discipline Sprint, originating out of a long inacceptance of the Sprint in the World-Cup (WC), the late invention in the world championships (Lahti 2001 skating, Oberstdorf 2005 classic) and Olympic Games (Salt Lake City 2002), different approaches in the control of training, the use of training methods and technique can be observed. Up to present there is a lack of published investigations about loading (physiological, biomechanical), demand and predictors of performance for the XC-Sprint. Thus, most knowledge is based on coaches` experiences or adapted from studies in other sports like sprint and middle-distance running. In contrast to running in athletics, in the XC-Sprint not only a single run is necessary but a high performance stability over 4 heats (1-1.5km each) over a time of 3 to 4 hours. Test concepts especially for the XC-Sprint are rarely and mostly not investigated on their reliability and validity. The specific aims of the study were 1) to develop a sprint simulation using roller skis on the treadmill, 2) to perform an analysis of loading of a XC-Sprint competition and 3) to examine relationships of measured biomechanical and physiologic variables with sprint performance.